Pine afforestation improves the biological soil attributes linked to methane oxidation in a temperate zone of Argentina - Teran, Ezequiel Jesús (2022)
Background: Atmospheric methane (CH4 ) is responsible for approximately 20% of global warming since the preindustrial era. Forests are land ecosystems whose role is crucial for mitigating the greenhouse effect due to their capacity to capture and store C and preserve other processes such as CH4 oxidation in the soil. On the other hand, in the particular case of afforestation, there are contradictory results about the magnitude of CH4 uptake variation due to changes in methanotrophic bacteria activity and its relationship with micro-environmental conditions. Results: The average potential CH4 oxidation rate in the laboratory (MOL) of afforested soil was 186% greater than that of the grassland, which could be marginally attributed to differences in soil physicochemical parameters like bulk density, pH and organic matter. A seasonal pattern in MOL was observed in both land uses, with the highest values at the warm and rainy season. MOL magnitude increased with soil depth up to 10-15 cm, which corresponds with the mineral layer. Conclusion: Pine afforestation would improve the biological soil attributes linked to methane oxidising bacteria compared to the grassland systems.